If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2x + 4) = 9x Reorder the terms: -5(4 + 2x) = 9x (4 * -5 + 2x * -5) = 9x (-20 + -10x) = 9x Solving -20 + -10x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -20 + -10x + -9x = 9x + -9x Combine like terms: -10x + -9x = -19x -20 + -19x = 9x + -9x Combine like terms: 9x + -9x = 0 -20 + -19x = 0 Add '20' to each side of the equation. -20 + 20 + -19x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -19x = 0 + 20 -19x = 0 + 20 Combine like terms: 0 + 20 = 20 -19x = 20 Divide each side by '-19'. x = -1.052631579 Simplifying x = -1.052631579
| 21+x=-5 | | -2x^2-7x+42=0 | | 8i+16.2=1.8 | | 4x+5+2x-11=180 | | a^2x+11ax+28x=0 | | -7x+4(x-3)=-33 | | 17.5*4= | | X+5+y=180 | | -9=a(9-5t) | | X+5+3x+5+y+2y+15=360 | | 7t-4=10n+14 | | 3.8y+8x=6 | | -8x=-4(x-4) | | 2(2x-4)-x-3=-14 | | log(8x+6)=1 | | 6(3n+2)=9(5n+9)+2 | | X+5+3x+5+y+2y+15=180 | | x^2+4x+161=0 | | -2a-9=6x+15 | | -3x-45=-11x+51 | | f(x)=-12x+48 | | .3x-2.3=.1 | | 2(4y-3)=-10 | | -7w+2(w+4)=3 | | 8+x=-21 | | -32+t+18= | | 5y+12=57 | | 12=x^2-4 | | 10x+y=7(x+y) | | -25+2v=-56v-42 | | 50c+5f+10cr+fr=0 | | r^2-r+2=7 |